Catastrophic cerebral infarction during extracorporeal life support due to a rare anomaly in the circle of Willis. (5th July 2019) - Sonobe, Aiko; Kato, Hideyuki; Mathis, Bryan J; Hiramatsu, Yuji
Abstract: During extracorporeal life support (ECLS) in infants, cannulation of the right common carotid artery may result in a devastating ischaemic neurological injury. Herein, we present a case of an infant who encountered bilateral cerebral infarction during ECLS via the right carotid artery due to a rare and tragic anomaly of the circle of Willis. The magnetic resonance angiography complemented computed tomography in diagnosing the infarction and identifying this unique anatomy.